The relationship between geriatric patients’ nutritional status and depression: the case of Turkey: Geriatric patients' nutritional status and depression - Son, Nazan (Progress in Nutrition, 2023)
Introduction: This study was planned to investigate the relationship between the nutritional status and the development of depression of the older adult population living in their own settings in Eskisehir, Turkey.Materials and Methods: This study was carried out with 129 individuals aged 65 and over (40.3% male, 59.7% female) who visited a private health institution in Eskisehir. This single-centre cross-sectional study was conducted between October 1-December 1, 2021. The Mini Nutritional Assessment (MNA) and Geriatric Depression Scale (GDS) were applied to the older adults with the face-to-face interview technique after their anthropometric and biochemical measurements were taken.Results: The mean age of the participants was found 71.15±5.95 years. Among the participants, 2.3% of them were determined to have malnutrition, 34.2% were at malnutrition risk, and 63.5% had a normal nutritional status. As per the GDS results, 45.7% of the older adults participating in the study were found to have depression.Conclusion: Determining the nutritional status and providing solution options is an important parameter in terms of reducing the risk of disease in individuals aged 65 and over in societies. The results of our study showed that there is a linear relationship between malnutrition developing due to inadequate nutrition and the development of depression and that they might trigger each other. MNA and GDS should be used as routine screening tools for populations aged 65 and over in all societies, and emergency action plans should be implemented to improve the living comfort of older adults in line with the results.